Variety of immune responses to chronic stress in rats male - Polovynko, Іlona S; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Background. Previously we have been carry out integrated quantitative estimation of neuroendocrine and immune responses to chronic restraint stress in male rats. Revealed that the value of canonical discriminant roots rats subjected to chronic stress different not only on the values of intact animals (by definition), but also among themselves. So we set a goal retrospectively divided stressed rats into three homogeneous groups. Material and methods. The experiment is at 50 white male rats. Of these 10 animals not subjected to any influences and 40 within 7 days subjected to moderate stress by daily 30-minute immobilization. The day after the completion of stressing in portion of the blood immunological parameters were determined by tests I and II levels of WHO. The spleen and thymus did smears for counting spleno- and thymocytograms. Results. The method of cluster analysis (k-means clustering) formed three groups-clusters. For further analysis selected 18 parameters that members of each cluster differing minimum and maximum are different from members of other clusters (η2=0,73÷0,15; F=49,0÷3,26; p=10-6÷0,05). We stated that in 16 rats from cluster III the deviation 16 parameters in either side of the average norm almost identical and are in an acceptable range of ±0,5σ. Thus, the immune status of 40% of the rats subjected to moderate chronic stress was resistant to its factors. For the immune status of the 15 (37,5%) rats cluster II typical moderate inhibition microphage, killer and T-cellular links in combination with a strong activation macrophage link. Poststressory changes in immunity in 9 rats (22,5%) from cluster I differ from those in cluster II both qualitatively and quantitatively. In particular, the rats in this cluster were found no deviations from the norm or reaction blast transformation T-cells nor NK-lymphocytes levels. However, other parameters of T-link and microhage link suppressed more and settings macrophage link appeared activated very significantly, and the area of activation, except thymus and blood, spread to the spleen. Conclusion. We assume that a variety of immune responses to chronic stress caused by a variety of reactions neuroendocrine factors.